Uma poética em um ato: o teatro crítico de Caio Fernando Abreu - Paula, Marcela Oliveira de (2017)
Caio Fernando Abreu gained relevance in the Brazilian literature scene mainly due to his fruitful accomplishments as a fictionist, operating a critique of the forms of oppression in the decades of 1970, 1980 and 1990. However, although mildly known, his dramaturgy (as well as his narratives) intimately converses with many elements of the cited period: military authoritarianism, the growth of social movements, patriarchal values and violence, among others. Through the analysis of two plays from his Teatro completo, this thesis proposes to investigate how Caio’s drama production deals with contemporary issues, be it in the thematic sphere or in the formal level. With this finality, brings to bear some of the voices in the gaucho writer’s critical fortune so as to identify the strong aspects of his works, puts into focus some of his letters related to the theatrical theme in order to understand how the writer’s dramatist facet was built, revisits Brazilian theatre from the 1960s to the 1980s with a brief overview, and puts into analytical perspective Pode ser que seja só o leiteiro lá fora, from 1973, and Zona Contaminada, which had its first version concluded in 1978 and a last one in 1993, when it finally reaches the stages. With the structural analysis of both plays – emphasizing, in the first, the musical aspect and, in the second, the male oppression –, based on a theoretical framework that studies the text and the theatrical spectacle, it is observed that Caio Fernando Abreu composes a critical drama, anchored primarily in the form of a one act play, which offers essential characteristics for the author’s proposed level of criticism in his dramatic oeuvre.